2014
DOI: 10.1590/s1677-5538.ibju.2014.04.07
|View full text |Cite
|
Sign up to set email alerts
|

The merits of cytology in the workup for upper tract urothelial carcinoma - a contemporary review of a perplexing issue

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Introduction: The importance of upper tract cytology for evaluating tumors is unclear. We correlated upper tract cytology with histologic findings in patients who underwent nephroureterectomy for upper tract urothelial carcinoma (UTUC) at a single tertiary care referral center. Materials and Methods: 137 patients underwent nephroureterectomy between 2004and 2012. 18 patients were excluded (benign tumors, atrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Grade categories in cytology and histology do not always precisely predict the behaviour of UC, since aggressive low-grade UC exists. Cytological grading and categorisation of neoplastic cells from UUT can be particularly challenging, since the atypia tends to be more subtle even in neoplasms that behave aggressively 26 27. For endoscopically visible tumours in the UUT, the diagnosis of urothelial neoplasia usually suffices for further management since an excision of these tumours is aimed regardless of their grading, which is not considered as a strong prognostic factor in the UUT 28.…”
Section: Discussionmentioning
confidence: 99%
“…Grade categories in cytology and histology do not always precisely predict the behaviour of UC, since aggressive low-grade UC exists. Cytological grading and categorisation of neoplastic cells from UUT can be particularly challenging, since the atypia tends to be more subtle even in neoplasms that behave aggressively 26 27. For endoscopically visible tumours in the UUT, the diagnosis of urothelial neoplasia usually suffices for further management since an excision of these tumours is aimed regardless of their grading, which is not considered as a strong prognostic factor in the UUT 28.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the false negative rate of diagnosing HGUC using UUT cytological specimens was approximately 26% using non‐TPS classification system . By contrast, the false negative rates varied wildly from 10% to as high as 31% when applying TPS to LUT cytological specimens .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently demonstrated a higher accuracy rate for the detection HGUC and/ or muscle-invasive tumors (pT2-pT4) compared with LGUN and/or non-muscle invasive tumors (pTa-pT1) in UUT cytology. 22,26,29,32,33,39,45,48 However, Sverrisson et al 27 reported that abnormal UUT cytology was not predictive of tumor grade or disease stage.…”
Section: Pre-tps Evaluation Of Uut Cytologymentioning
confidence: 99%